Cost-benefit analysis and sustainability considerations in starting a restaurant: A case study from Sri Lanka - Sahan Perera; Dunith Abeyaratne; Kavindu Nimesh; Sakith Dewnith; Yasas Sri; Methuli Mewanya; Haritha Perera; Kavindi Wathsala; Sarasi Perera; Thilina Jayathilaka; Nuwan Jayarathna (Economics, Management and Sustainability)
Purpose: The primary purpose of this paper is to evaluate the financial viability and sustainability of launching a new vegetarian restaurant, "Tandoori Tales," in Sri Lanka, using a comprehensive cost-benefit analysis. The study aims to provide actionable insights for entrepreneurs and stakeholders in the hospitality sector, with a particular focus on sustainable business practices. Methodology: The research employs a case study approach, integrating detailed financial modeling, cost and revenue projections, and break-even analysis. The analysis includes both quantitative (financial calculations using Python and Matplotlib) and qualitative (market positioning, eco-friendly strategies) methods to assess the feasibility and sustainability of the business. Results: The findings indicate that "Tandoori Tales" can achieve financial sustainability within the first year of operation, with a projected net profit margin of 15.2% and a break-even point reached within 10 months. The adoption of eco-friendly practices, such as waste reduction, portion control, and the use of technology for inventory management, further enhances the restaurant's operational efficiency and aligns with the United Nations' Sustainable Development Goals. Theoretical Contribution: The paper contributes to the literature on entrepreneurship and sustainable business by demonstrating how rigorous cost-benefit analysis, coupled with sustainability-driven strategies, can inform successful SME start-ups in emerging markets. It bridges the gap between financial planning and sustainable management in the restaurant industry. Practical Implications: This study provides a replicable framework for aspiring entrepreneurs and policymakers to assess the viability of new ventures in the hospitality sector. It underscores the importance of integrating sustainability considerations – such as responsible resource use, waste management, and employee welfare – into business planning to enhance long-term success and contribute to the achievement of the Sustainable Development Goals (SDGs).